PENGARUH PENYULUHAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI DI SMK NEGERI 3 RAMBAH - Hikmah, Nurul; Bewelli Fahmi, Yuyun (AHM Center, 2026)
Globocan data from 2020 by the World Health Organization (WHO) shows that the number of new breast cancer cases reached 68,858 cases (16.6%) out of a total of 396,914 new cancer cases in Indonesia. One of the appropriate efforts in early detection of breast abnormalities, especially breast cancer, is by performing a breast self-examination. (SADARI). The purpose of this research is to determine the effect of health education on breast self-examination on the knowledge of female adolescents about Breast Self-Examination (SADARI) at SMK Negeri 3 Rambah. The type of research used is experimental research with a pretest-posttest group design approach, which involves conducting a pretest (initial observation), followed by providing counseling to a group, and then conducting a posttest (final observation) using total sampling technique with a sample size of 20 people by administering 20 questions through a questionnaire. Data analysis in this study used the Paired Sample T-Test statistical test. The results showed an influence of counseling on the knowledge of adolescent girls (p value = 0.000 <0.05). This study indicates that counseling has an effect on the knowledge of adolescent girls about breast self-examination (SADARI) at SMK Negeri 3 Rambah. Health counseling about SADARI needs to be continued with a larger number of respondents, especially adolescent girls, as an effort to increase their knowledge about SADARI to detect early signs of lumps or abnormalities in the breasts.